Daphnia magna responses to fish kairomone and chlorpromazine exposures. (1st July 2020) - Alkimin, Gilberto Dias de; Nunes, Bruno; Soares, Amadeu MVM.; Bellot, Marina; Gómez-Canela, Cristian; Barata, Carlos
Abstract: To avoid being preyed, organisms must be able to identify predatory threats by sensing molecules released by predators (kairomones), and to employ effective strategies to prevent detection by predators. Furthermore, in the wild, organisms are also exposed to chemicals that may alter their behavioral traits, such as neuroactive pharmaceuticals. Considering the co-occurrence of both types of chemicals, their possible interaction needs to be studied. To address this topic, the aim of this study was to verify the effects of fish kairomone (FK – a chemical associated to putative predation by fish) and chlorpromazine (CPZ - neuroactive pharmaceutical drug, environmental contaminant), isolated and in combination, in different functional endpoints of Daphnia magna, such as oxygen consumption, feeding rate, behavior and reproduction. Among these endpoints, oxygen consumption was only affected by the combination of compounds (FK + CPZ). On the other hand, feeding rate was affected by all treatments, being lower than control. For life history traits and phototactic behavior, the effects of FK predominated over the ones caused by CPZ exposure, incrementing the reproductive output of females, leading to greater population growth rates and increasing negative phototactic behaviour. Graphical abstract: Image 1 Highlights: Chlorpromazine (CPZ) and Fish kairomone (FK) caused functional alteration in D. magna . Feeding rate was decreased in all treatment conditions. Oxygen consumption was only affected in the mixture treatment (CPZ + FK). For life history traits and phototactic behavior the effects of FK dominated those of CPZ.